1981
DOI: 10.1083/jcb.90.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent low density lipoprotein for observation of dynamics of individual receptor complexes on cultured human fibroblasts.

Abstract: The visible wavelength excited fluorophore 3,3'-dioctadecylindocarbocyanine iodide (dil[3]) was incorporated into human low density lipoprotein (LDL) to form the highly fluorescent LDL derivative dil(3)-LDL . Dil(3)-LDL binds to normal human fibroblasts and to human fibroblasts defective in LDL receptor internalization but does not bind to LDL receptornegative human fibroblasts at 4°C or 37°C . It is internalized rapidly at 37°C by normal fibroblasts and depresses the activity of 3-hydroxy-3-methylglutaryl coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(58 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…There may only be a minimum of 32 copies of a particular kinetochore protein per spindle pole of a diploid yeast strain, assuming one copy per chromosome (Lechner and Carbon, 1991). Work in other systems suggests that such a copy number should be detectable if the molecules are in close proximity: for example myosin minifilaments containing 8 molecules can be detected by immunofluorescent staining with a mAb against the myosin head (Yonemura and Pollard, 1992), while around 50 molecules of a fluorescent cyanine dye were detected when bound to low density lipoprotein on the surface of a cell (Barak and Webb, 1981). In our case 32 copies of protein would have around a thousand molecules of FITC bound assuming threefold amplification by both first and second antibodies and with four moles of FITC per mole of second antibody.…”
Section: Localization Of Ndcl0pmentioning
confidence: 99%
“…There may only be a minimum of 32 copies of a particular kinetochore protein per spindle pole of a diploid yeast strain, assuming one copy per chromosome (Lechner and Carbon, 1991). Work in other systems suggests that such a copy number should be detectable if the molecules are in close proximity: for example myosin minifilaments containing 8 molecules can be detected by immunofluorescent staining with a mAb against the myosin head (Yonemura and Pollard, 1992), while around 50 molecules of a fluorescent cyanine dye were detected when bound to low density lipoprotein on the surface of a cell (Barak and Webb, 1981). In our case 32 copies of protein would have around a thousand molecules of FITC bound assuming threefold amplification by both first and second antibodies and with four moles of FITC per mole of second antibody.…”
Section: Localization Of Ndcl0pmentioning
confidence: 99%
“…This tool would be particularly valuable when the tissue preparation can not be dispersed for analysis by flow cytometry, or when morphological information contributes to the overall analysis, or when there is a need to reanalyze the cells after a conventional histological stain has been applied to the specimen. Fluorescence image cytometry has an advantage over transmitted light cytometry both in the sensitivity of detection (1) and the ability to analyze many different color fluorescent markers simultaneously. For example, two transmitted light colors, Feulgen stained nuclei and peroxidase deposits, can be quantified simultaneously, but up to four different fluorescent markers can be analyzed on a single sample, as we show in this work.…”
Section: Discussionmentioning
confidence: 99%
“…The question was whether the JD-LDL-R is unusually immobile. In labeling the LDL-R, we found that LDL itself could absorb up to 30 copies of a carbocyanine fluorophore and become so brightly labeled that we could track its trajectories on the living cell surface for many minutes (22). The LDL-R did show remarkably slow diffusion on living cell surfaces, where it stayed with little internalization.…”
Section: Cell Surface Molecular Mobilitiesmentioning
confidence: 91%